Intergrating Problem-Based Learning and Team-Based Learning (PITBL) in Nursing Students: A Pilot study - Yossi Indra Kusuma; Gandes Retno Rahayu; Savitri Shitarukmi (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2017)
Background: Change seems to be a constant in education. The shifting paradigm from teacher-centered to student-centered impact on demands of medical and health professions education institution to undertake curricullum reform. The development of PBL requires the provision of resources needed for its implementation. The emergence of newly developed method, TBL, garnered interest because of its potential to promote active learning without requiring large numbers of resources. The integration of these two methods can complement each deficiencies with their advantages, so it can optimize student learning. This study is aimed to determine the impact of the integration of PBL and TBL (PiTBL) on student engagement and to evaluate the perceptions of students in terms of accountability, preferences and their satisfaction with this method.Method: This study was a pre-experimental with one group pre and post test design. Subjects consisted of 103 nursing students who enrolled Fluid, Electrolyte an Elimination course. The collection of data before and after the intervention were held to determine the difference in student engagement, using “Classroom Engagement Survey” instrument from Baylor University. Students perceptions in terms of accountability, preference and satisfaction were measured with PiTBL-Student Assessment Instrument (PiTBL-SAI).Results: PiTBL had a positive impact on student engagement, but its results were lower then PBL. The difference was not significant for participation sub-scale, and significant in several weeks of course for enjoyment sub-scale and total value of student engagement. Students perceptions in terms of accountability, preference and their satisfaction with PiTBL all showed positive results.Conclusions: PiTBL had a positive impact on student engagement, although lower than PBL. Students perceptions in terms of their accountability, preference and satisfatction with this method is also positive. We concluded that this method can be used as an alternative in implementing an effective and eficient active learning method.